Ablation guided by STAR‐mapping in addition to pulmonary vein isolation is superior to pulmonary vein isolation alone or in combination with CFAE/linear ablation for persistent AF. (9th January 2021) - Honarbakhsh, Shohreh; Schilling, Richard J.; Providencia, Rui; Dhillon, Gurpreet; Bajomo, Omotomilola; Keating, Emily; Finlay, Malcolm; Hunter, Ross J.
Abstract: Introduction: The optimal ablation approach for persistent atrial fibrillation (AF) remains unclear. Methods and Results: Objective was to compare the long‐term rates of freedom from AF/AT in patients that underwent STAR mapping guided ablation against outcomes of patients undergoing conventional ablation procedures. Patients undergoing ablation for persistent AF as part of the Stochastic Trajectory Analysis of Ranked signals (STAR) mapping study were included. Outcomes following 'pulmonary vein isolation (PVI) plus STAR mapping guided ablation (STAR mapping cohort) were compared to patients undergoing PVI alone ablation during the same time period and also a propensity‐matched cohort undergoing PVI plus the addition of complex fractionated electrogram (CFAE) and/or linear ablation ("conventional ablation"). Rates of procedural AF termination and freedom from AF/AT during follow‐up were compared. Sixty‐five patients were included in both the STAR cohort and propensity matched conventional ablation cohort. AF termination rates were significantly higher in the STAR cohort (51/65, 78.5%) than conventional ablation cohort (10/65, 15.4%) and PVI alone ablation cohort (13/50, 26.0%; STAR cohort vs. other 2 cohorts both p  < .001). There was no significant difference in procedure time between the three cohorts. During ≥20 months follow‐up a lower proportion of patients had AF/AT recurrence in the STAR cohort (20.0%) compared with the conventional ablation cohort (50.8%) or the PVI alone ablation cohort (50.0%; both p  < .05 compared to STAR cohort). Conclusions: Outcomes of PVI plus STAR mapping guided ablation was superior to PVI alone or in combination with linear/CFAE ablation. A multicenter randomized controlled trial is planned to confirm these findings.